STATUS PARITAS DENGAN TEKNIK MENYUSUI PADA IBU POST PARTUM - Pasiak, Sri Meyke; Pinontoan, Odi; Rompas, Sefty (JURNAL KEPERAWATAN, 2019)
Abstract:Breastfeeding is the ideal way for mom to express affection on her daughter and the best way for mom to paint food full of nutrients, but the reality is still a lot of mothers who cannot breastfeed by breastfeeding Technique. Methods this study used a cross-sectional research design cros with entire population mother post!, in Clinics And health centers in Manado Tuminting Wori Minut, using primary data interviews and observations as well as secondary data obtained from the clinic. Samplingis done in a non probability sampling with pruposive samplingtechniques. The number of samples as many as 47 respondents. The data presented in the form of a Frequency Table, the analysis of the data used is the analysis of univariate and bivariat analysis method using chi-square. Research results based on the characteristics of the mother post!, respondents have age 19-25 years, educated in high school, and worked as the IRT Primipara and Multipara parity with, the majority of respondents who do good on nursing Techniques parity multipara (59.6%), sedangankan respondents who do less good feeding Techniques on primipara parity. Test results of chisquare. Get results in a value of p = 0.01 smaller than Î± = 0.05. In conclusion, the results of this study showed no connection between status which meant parity with the technique of breastfeeding on maternal post. Keywords:Status Of Parity, Breastfeeding Techniques Abstrak: Menyusui merupakan cara yang ideal bagi ibu untuk mengekspresikan kasih sayang pada anaknya dan cara terbaik bagi ibu untuk memberikan makanan yang penuh gizi, namun kenyataan masih banyak ibu yang tidak dapat menyusui dengan teknik menyusui yang benar. Metode penelitian ini menggunakan desain penelitian cros sectional dengan populasi seluruh ibu post partum di Puskesmas Tuminting Manado Dan Puskesmas Wori Minut, dengan menggunakan data primer wawancara dan observasi serta data sekunder yang didapat dari pihak Puskesmas. Pengambilan sampel dilakukan secara non probability sampling dengan teknik pruposive sampling. Jumlah sampel sebanyak 47 responden. Data disajikan dalam bentuk Frequency Table, Analisis data yang digunakan adalah analisis univariat dan bivariat dengan menggunakan metode analisis chi-square. Hasil penelitian berdasarkan karakteristik ibu post partum, responden memilki usia 19-25 tahun, Berpendidikan SMA, dan bekerja sebagai IRT dengan paritas Multipara dan Primipara, mayoritas responden yang melakukan Teknik menyusui yang baik pada paritas multipara (59,6%), sedangkan responden yang melakukan teknik menyusui yang kurang baik pada paritas primipara. Dari hasil ujichisquaredidapatkan hasil nilai p = 0,01 lebih kecil dari Î± = 0,05. Kesimpulan, hasil penelitian ini menunjukan ada hubungan yang bermakna antara status paritas dengan teknik menyusui pada ibu post partum. Kata Kunci:Status Paritas, Teknik Menyusui